2013
DOI: 10.1097/brs.0b013e318271319c
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Mode, and Location of Acute Proximal Junctional Failures After Surgical Treatment of Adult Spinal Deformity

Abstract: APJFs were identified in 5.6% of patients undergoing surgical treatment of adult spinal deformity, with failures occurring primarily in the TL region of the spine. There is evidence that the mode of failure differs depending on the location of UIV, with TL failures more likely due to fracture and UT failures more likely due to soft-tissue failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
189
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 248 publications
(196 citation statements)
references
References 13 publications
4
189
3
Order By: Relevance
“…In a large multi-center, retrospective study consisting of adult deformity patients, Hostin et al [2] defined PJK as the Cobb angle formed by the lower endplate of the UIV and the upper endplate of two supra-adjacent vertebrae above the UIV 15°or greater. O'Shaughnessy et al [14] and Bridwell et al [15] used 20°as their cutoff value.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large multi-center, retrospective study consisting of adult deformity patients, Hostin et al [2] defined PJK as the Cobb angle formed by the lower endplate of the UIV and the upper endplate of two supra-adjacent vertebrae above the UIV 15°or greater. O'Shaughnessy et al [14] and Bridwell et al [15] used 20°as their cutoff value.…”
Section: Definitionmentioning
confidence: 99%
“…In contrast, symptomatic PJK is frequently encountered in children with early onset scoliosis who undergo fusionless surgery (e.g., growing rod), often necessitating revision surgery. In addition to the disc change, PJK in adults also includes fractures, subluxations, and long sweeping kyphosis above the fusion [1][2][3][4][5][6][7][8]. This can lead to proximal junction failure causing pain, deformity, instability, and implant prominence, with a risk of neurological deficit.…”
Section: Introductionmentioning
confidence: 95%
“…22,24 However, a subset of PJK, known as "proximal junctional failure" (PJF), has recently been identified as a more severe form of PJK that is associated with an increased need for revision surgery. 4,15,16,18,35,47,48,51 PJF is defined as a > 10° change of kyphosis between the UIV and the vertebra 2 levels above the UIV (UIV+2), along with a fracture in the vertebral body of UIV or UIV+1 and/or a disruption of the posterior osseoligamentous complex and/or pullout of instrumentation at the UIV. 4,15,16,18,35,47,48,51 Even though both PJK and PJF are defined, at least partly, by an increased proximal kyphosis, PJF is thought to represent an entity distinct from PJK with differing pathology and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…4,15,16,18,35,47,48,51 PJF is defined as a > 10° change of kyphosis between the UIV and the vertebra 2 levels above the UIV (UIV+2), along with a fracture in the vertebral body of UIV or UIV+1 and/or a disruption of the posterior osseoligamentous complex and/or pullout of instrumentation at the UIV. 4,15,16,18,35,47,48,51 Even though both PJK and PJF are defined, at least partly, by an increased proximal kyphosis, PJF is thought to represent an entity distinct from PJK with differing pathology and risk factors. Specifically, PJF appears to result from an acute event rather than from a recurrent deformity 15,48 and has been shown to have a strong association with preoperative spinopelvic mismatch, increased SVA, and increased thoracic kyphosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hostin et al reported a 5.6% incidence of acute PJK. 12 An advantage of fusion to the UT spine is that the UT segments surrounded by the rib cage and the scapulae are the most stabilized segments in the thoracic spine. 8 However, our data suggest that the stress caused by the deformity correction was distributed over fewer motion segments (only in the cervicothoracic spine) in the UT group than in the LT group (in the thoracic spine and cervicothoracic spine).…”
mentioning
confidence: 99%